2018
DOI: 10.5892/ruvrd.v16i1.4912
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho De Frangos De Corte Criados Em Aviário Convencional E Dark-House

Abstract: The brazilian poultry industry is one of the most developed in the world, however, with significant growth and scientific progress, studies are needed on accommodation and techniques for creating ambience of birds. An aviary should ensure a comfortable environment for poultry, ensuring high productivity. In this context, seeking to overcome the variations of ambience, it has adopted the construction of Dark-House aviaries with curtains and solid wall, which provide a greater environmental control and improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
3
0
2
Order By: Relevance
“…When evaluating the final slaughter weight between the two treatments, we found that the chicks in the negative pressure unit achieved higher body weight. Similar results were reported by Andreazzi et al (2018), who reported that negative pressure aviaries with a curtain and a solid wall produced greater slaughter weight in relation to the conventional aviary equipped with a positive pressure system. The same was observed in the study by Verdi (2009), in which the highest weights and the lowest food conversion were observed in the dark house system with curtain (negative pressure), when compared to the positive pressure system.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When evaluating the final slaughter weight between the two treatments, we found that the chicks in the negative pressure unit achieved higher body weight. Similar results were reported by Andreazzi et al (2018), who reported that negative pressure aviaries with a curtain and a solid wall produced greater slaughter weight in relation to the conventional aviary equipped with a positive pressure system. The same was observed in the study by Verdi (2009), in which the highest weights and the lowest food conversion were observed in the dark house system with curtain (negative pressure), when compared to the positive pressure system.…”
Section: Discussionsupporting
confidence: 89%
“…The same was observed in the study by Verdi (2009), in which the highest weights and the lowest food conversion were observed in the dark house system with curtain (negative pressure), when compared to the positive pressure system. Our results, as well as those of Andreazzi et al (2018) and Verdi (2009) suggest that the technology applied in the new aviary models, in which the air conditioning systems are based on negative pressure, guarantees less chance of error in the environment, because they produce environments with greater control, as opposed to conventional poultry houses that use positive pressure. By contrast, Vigoderis et al (2010) in the same climate region; reported that unventilated (positive pressure) units produced larger chickens than those raised in positive pressure units using fans that were used to remove gases and dust from within the facility.…”
Section: Discussionsupporting
confidence: 74%
“…Farmers are adjusting the broiler chickens barn from conventional to a dark environment (Dark House) due to achieve better performance. However, such a condition could affect meat exports because natural light can be a further welfare rule (Andreazzi et al, 2018). Related to animal welfare, Brazil does not have any legislation in the welfare of broiler chickens, e.g., regulation on the density of broiler chickens (Van Horne & Achterbosch, 2008).…”
Section: Effect Of Environmental Enrichment On the Body Weight In Bromentioning
confidence: 99%
“…Late red light for birds appears to contribute to lightest bone weight, bone strength, and body weight. Andreazzi et al (2018) observed that broiler chickens in a conventional broiler house presented an average of 2.720 kg and 2.806 kg in a broiler house with a dark curtain (Dark House). Farghly et al (2019) observed that broiler chickens exposed to flashing light and an intermittent feeding regime had the highest body weight and lowest feed conversion rate when compared with the control treatment.…”
Section: Effect Of Environmental Enrichment On the Body Weight In Bromentioning
confidence: 99%
“…Neste sistema o ar é sugado de dentro para fora da instalação por exaustores criando um vácuo parcial dentro do aviário, as cortinas permanecem sempre fechadas e precisam ter boa vedação, para que só haja entrada de ar pela placa evaporativa, isso garante uma maior eficiência dos exaustores e melhor conforto térmico dentro do galpão (Oliveira & Gai, 2016). Na entrada do ar do aviário são instaladas placas evaporativas (pad cooling), que geralmente são utilizados blocos cerâmicos ou painéis de celulose (mais eficiente), onde a água circula e quando o ar quente passa pela água na placa, transfere o calor para a água, evaporando-a, entrando com uma temperatura mais amena no interior do galpão (Andreazzi et al, 2018). Principalmente para esses modelos de aviários recomendase o uso de geradores de energia em caso de falta de energia, se os exaustores param de funcionar pode ocorrer desequilíbrio da temperatura interna, causando estresse excessivo e morte das aves.…”
Section: Acondicionamento Climatizado Por Pressão Negativaunclassified